MrpA Functions in Energy Conversion during Acetate-Dependent Growth of Methanosarcina acetivorans - Jasso-Chávez, Ricardo (American Society for Microbiology, 2013)
The role of the multisubunit sodium/proton antiporter (Mrp) of Methanosarcina acetivorans was investigated with a mutant deleted for the gene encoding the MrpA subunit. Antiporter activity was 5-fold greater in acetate-grown versus methanol-grown wild-type cells, consistent with the previously published relative levels of mrp transcript. The rate, final optical density, and dry weight/methane ratio decreased for the mutant versus wild type when cultured with a growth-limiting concentration of acetate. All growth parameters of the mutant or wild type were identical when grown with methanol in medium containing a growth-limiting Na(+) concentration of 1.04 M. The lag phase, growth rate, and final optical density for growth of the mutant were suboptimal compared to the wild type when cultured with acetate in medium containing either 0.54 or 1.04 M Na(+). The addition of 25 mM NaCl to resting cell suspensions stimulated ATP synthesis driven by a potassium diffusion potential. ATP synthesis was greater in wild-type than mutant cells grown with acetate, a trend that held for methanol-grown cells, albeit less pronounced. Both sodium and proton ionophores reduced ATP synthesis in the wild type grown with either substrate. The results indicated that the Mrp complex is essential for efficient ATP synthesis and optimal growth at the low concentrations of acetate encountered in the environment.